Leading from the middle : a playbook for managers to influence up, down, and across the organization - Mautz, Scott (Wiley, 2021)
"Leading from Middle is the only playbook designed specifically to help the middle manager be more effective in in managing up, down, and across his or her organization. The book will provide actionable, step-by-step instruction for the daily challenges a middle manager may face, including: extracting more resources from management; better communicating corporate initiatives to direct reports; influencing peers and colleagues; navigating times of changes; and much more. Leading from the Middle takes the lessons of Dale Carnegie's "How To Win Friends and Influence People" and John C. Maxwell's "360 Leadership" and distills them into an accessible handbook designed for daily reference."--